Characterization of Iron Oxide Nanotubes Obtained by Anodic Oxidation for Biomedical Applications—In Vitro Studies - Rangel, Rita de Cássia Reis [UNESP]; Rangel, André Luiz Reis [UNESP]; da Silva, Kerolene Barboza [UNESP]; Escada, Ana Lúcia do Amaral [UNESP]; Chaves, Javier Andres Munoz; Maia, Fátima Raquel; Pina, Sandra; Reis, Rui L.; Oliveira, Joaquim M.; Rosifini Alves, Ana Paula [UNESP] (MDPI, 2024)
To improve the biocompatibility and bioactivity of biodegradable iron-based materials, nanostructured surfaces formed by metal oxides offer a promising strategy for surface functionalization. To explore this potential, iron oxide nanotubes were synthesized on pure iron (Fe) using an anodic oxidation process (50 V–30 min, using an ethylene glycol solution containing 0.3% NH4F and 3% H2O, at a speed of 100 rpm). A nanotube layer composed mainly of α-Fe2O3 with diameters between 60 and 70 nm was obtained. The effect of the Fe-oxide nanotube layer on cell viability and morphology was evaluated by in vitro studies using a human osteosarcoma cell line (SaOs-2 cells). The results showed that the presence of this layer did not harm the viability or morphology of the cells. Furthermore, cells cultured on anodized surfaces showed higher metabolic activity than those on non-anodized surfaces. This research suggests that growing a layer of Fe oxide nanotubes on pure Fe is a promising method for functionalizing and improving the cytocompatibility of iron substrates. This opens up new opportunities for biomedical applications, including the development of cardiovascular stents or osteosynthesis implants.
Keywords: biodegradable biomaterials; biodegradable metal; surface modification